Design and analysis of transmitter module for intra-body communication (IBC) based on health monitoring system / `Abdul Hakim Ayub, Abdul Karimi Halim and Abdul Hadi Abdul Razak - Ayub, Abdul Hakim; Halim, Abdul Karimi; Abdul Razak, Abdul Hadi (UiTM Press, 2014)
This paper presents the design and development of a transmitter module for a Body Area Network (BAN) health monitoring system based on Intra-Body Communication. Intra-body Communication (IBC) is a communication technique that uses the human body as a medium for electrical signal communication. One of the visions in the healthcare industry is to provide autonomous and continuous self and the remote health monitoring system. This can be achieved via BAN, LAN and WAN integration. The BAN technology itself consists of short range data communication modules, sensors, controller and actuators. The information can be transmitted to the LAN and WAN via the RF technology such as Bluetooth, ZigBee and ANT. There are several limitation of the current RF technology in IBC products such as high power consumption, low battery lifetime and high electromagnetic interference signal attenuations. One of the solutions for Medical Body Area Network (MBANs) to overcome these issues is by using an IBC technique because it can operate at lower frequencies and power consumption compared to the existing techniques. The main objectives is to design a low frequency IBC transmitter between range 21MHz to 24MHz by using discreet component. The specifications of the modules such as frequency, data rate, and modulation system will be defined. The individual module been designed and tested separately. The modules is integrated as an IBC transmitter system and tested for functionality then implemented on the PCB. The signals from the transmitter can be viewed via external devices such as oscilloscope. The signals such as heartbeats or pulses can also be displayed on LCD. In conclusion, all the sub-modules ADC, shift register, and modulation been tested in software simulation separately and operate correctly. For hardware testing ADC and shift register module work properly but BFSK modulator cannot produce exact frequency.